University living learning labs: an integrative and transformative approach - Zen, Irina Safitri; Souza, Clare D'; Ismail, Sarimah; Arsat, Mahyuddin (Penerbit Universiti Malaysia Terengganu (UMT), 2019)
Having the global movement of the University’s third mission of co-creation for sustainability, the living lab has mentioned as one of innovative and transformative approach for university response to the global environmental challenges of climate change. However, not much attention has been discussing in a more structured manner how the university function as living labs in the context of the societal learning process. The study analyses the extent of how the university can accommodate the living labs approach and educate the public in a larger agenda of the society learning process in the context education for sustainable development, ESD. What are suitable learning pedagogies that can accommodate the transformations process? What kind of approaches need to be adapted to generate more robust research output to translate sustainable development in the realm of sustainability science. By using broad definition of living labs, consider the UTM New Academia Learning Innovation, realizing the initiative from the Ministry of Education Malaysia to enhance the role of university to engage larger society in mainstreaming sustainable development and by referring to the Malaysia Educational Blueprint, the study came up with a more comprehensive and approach of university mobilizing sustainable development by fully utilizing his role and function in the context of Malaysia. Finally, this article outlines several important characteristics to determine the success of the university living labs by developing an integrative and transformative framework called the University living learning labs. The framework aims to strengthen the internal capacity in research, teaching and learning and campus operation and added the fourth element of univer